Cognitive load-dependent effects of HD-tDCS on the executive vigilance decrement: insights from aperiodic EEG activity - Hemmerich, Klara; Lupiáñez, Juan; Martín-Arévalo, Elisa; Cohen Kadosh, Roi (Frontiers in Cognition, 2026)
IntroductionThis study investigated cognitive-load-dependent effects of high-definition transcranial direct current stimulation (HD-tDCS) on the executive vigilance (EV) decrement and its modulation by aperiodic electroencephalography (EEG) markers. Given the relevance of vigilance for daily functioning and its susceptibility to decline over time, we examined whether HD-tDCS could counteract this decrement under varying cognitive demands.MethodsIn a between-participant design (N = 180), anodal HD-tDCS was applied over the right posterior parietal cortex (rPPC) during performance of a single-, dual-, or triple-task, with on-task EEG recorded pre- and post-stimulation. Power spectra were parametrized to extract aperiodic (non-oscillatory) components; the aperiodic exponent and offset across two frequency ranges (1–35 and 30–45 Hz).ResultsHD-tDCS induced a reduction in the aperiodic exponent within the 30–45 Hz range (i.e., flattening of the spectral slope), consistent with increased cortical excitation. This change was associated with a mitigated EV decrement under high task demand and an exacerbated decrement under low demand, suggesting a mechanistic link between changes in excitation/inhibition balance and behavioral outcomes. However, these effects reached significance only under a directional hypothesis and seemed to be obscured by a push-pull relationship with the aperiodic offset, indicating a more complex interaction between local excitability and broadband spectral dynamics. Baseline aperiodic markers did not significantly moderate the stimulation effect but predicted overall task performance, independent of stimulation.DiscussionThese findings suggest a mechanistic understanding of how endogenous neural activity, specifically, aperiodic EEG features, modulates brain stimulation outcomes. By demonstrating that HD-tDCS effects vary as a function of cognitive load and spectral dynamics, the study underscores the need for future research, centered on refined, state-sensitive stimulation protocols to mitigate the EV decrement.